The Letters of Wilkie Collins, Volume 1
XLI, 268 p.
Keywords: Wilkie Collins is the only leading Victorian novelist whose letters have not been published. This two-volume edition will thus fill a gaping hole in any assessment of one of the nineteenth century's most loved novelists. It is also extremely timely. Two recent biographies have re-assessed his private life and his literary achievements. His best known novels, The Woman in White and The Moonstone, continue to feature on television, and most of his thirty-odd novels are in print. This authorized edition covers more than 2,000 of Collins' letters.